Analisis Capaian Kompetensi Mahasiswa dalam Objective Structured Clinical Examination (OSCE) Semester Ganjil Tahun Ajaran 2017/2018 Fakultas Kedokteran Universitas HKBP Nommensen Medan - Jenny Novina Sitepu (Universitas HKBP Nommensen, 2020)
Backgroud: Clinical skills is one of competency as a doctor. Objective Structured Clinical Examination (OSCE) is an ideal way to assess clinical skills for undergraduated, graduated, and postdraduated clinical students. The low score in some OSCE station can be an input for teaching and curriculum improvement. This study aim to analyzed student competency achievement in first term in 2017/2018 academic year in Fakultas Kedokteran Universitas HKBP Nommensen. Methods: This study was qualitative study with descriptive design. The sample was OSCE score in first term in 2017/2018 academic year. Student achievement was the mean score of every student in all station in OSCE. Competency achievement was the mean of students score for every competency in OSCE. Next, the stations was categorized in practice/ procedure skills station and clinical reasoning skills station. Skills achievement was got form the mean of score (in percent) of procedure skills and clinical reasoning station. Indept interview with students and lectures was held to knowed their perception about OSCE. Results: Students’ achievement in OSCE of first term academic year 2017/2018 was 62.4% for 2015’s students, and 64.6% for 2016’ students. The lowest competency achievement of 2015’s students was diagnosis and differential diagnosis. For the 2016’s students, it was farmacology treatment. Practice/ procedure skills achievement in OSCE of first term academic year 2017/2018 was 61.34% (2015’s students) and 74.4% (2016’s students). The clinical reasoning skills achievement was 62.80% (2015’s students), and 58.77% (2016’s students). Based on indept interview, the things that make student’s achievement low were the clinical reasoning ability of students was still low, the standard patient that involved in OSCE didn’t acted properly, the students’ knowledge about medicine and prescription was poor, and there were lot of learning schedules and learning subjects that students must did and learned. Conclusions: Students’ achievement in OSCE of first term academic year 2017/2018 is need to be improved.